Soil Nutrient Availability and Enzyme Activities under Wheat-Green gram Crop Rotation as Affected by Rock Phosphate Enriched Compost and Inorganic Fertilizers - and K.K. Bandyopadhyay, P.C. Moharana, D.R. Biswas, A.K. Patra S.C. Datta, R.D. Singh, Lata (Journal of the Indian Society of Soil Science, 2014)
The aim of this study was to evaluate the effect of rock phosphate (RP) enriched rice straw compost, FYM and inorganic fertilizers on changes in nutrient availability and enzyme activities in soil during different physiological growth stages under a wheat-green gram crop rotation in an Inceptisol. The matured RP enriched compost contained higher bioavailable P as well as total P content compared to farmyard manure. Data revealed that application of inorganic fertilizers and RP enriched compost or FYM either alone or in combination resulted in significant build-up in soil organic carbon, mineral N, Olsen-P and NH4OAc-K as well as enzyme activities compared to unfertilized control plots during different physiological growth stages of wheat and green gram. Plot receiving 50% NPK+RP enriched compost resulted in 100.8, 95.2 and 100.0 per cent greater build-up in Olsen-P over unfertilized control in Â crown root initiation (CRI), flowering and maturity stage of wheat, respectively. Irrespective of treatments, build-up of mineral N, Olsen-P and NH4OAc-K decreased in all the growth stages of green gram as compared to values obtained in wheat. The dehydrogenase and phosphatase activities (alkaline and acid) were higher in flowering stage than maturity and CRI stages of wheat. While, higher enzyme activities were obtained during pod formation in green gram. The results demonstrated that enriched compost could be prepared using low-grade RP with rice straw and used as an alternate nutrient source for improving crop yields, maintaining soil nutrient availability and enzyme activities.